Performance Modelling Of Flap-Type Wave Energy Converter Array: Flaps With Various Dynamic Characteristics - Saeidtehrani, S. (author); Lavidas, G. (author) (The American Society of Mechanical Engineers (ASME), 2022)
Generally, it is expected that the total power of N energy converters in an array will be less than N times the power of a single operative converter. The goal of this paper is to enhance the oscillation of the flap-type WEC and consequently the energy extraction of the whole array in front of a coastal structure. Flaps in an array show different response patterns in terms of amplitude and frequency based on their dynamic characteristics, incoming wave frequencies, and the distance between the WECs. Through this work, different dynamic characteristics for each flap in combination with various distances between proximate flaps are investigated. An experimentally validated numerical model developed for the simulation of flap-type WEC operating as single and in an array is used for the simulation. The effects of dynamic characteristics and WEC distances on the response and power production are estimated and discussed in detail for a flap operating in an array of two and five. It is shown that by changing the distance between two flaps, the response is enhanced up to 20%. The findings suggest the most efficient ratio of dynamic characteristics of flaps in an array of two is having a period half to the incoming wave period. However, for an array of five, having staggered flaps with a period equal to the incoming wave period make a 4% increase in the overall response of each flap. Green Open Access added to TU Delft Institutional Repository ‘You share, we take care!’ – Taverne project https://www.openaccess.nl/en/you-share-we-take-care Otherwise as indicated in the copyright section: the publisher is the copyright holder of this work and the author uses the Dutch legislation to make this work public. Offshore Engineering